FAKTFAKTOR YANG BERHUBUNGAN DENGAN USIA MENARCHE PADA SISWI SMP NEGERI 3 SUMBUL TAHUN 2014 - Fidrin Eni S Sipayung; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACTMenarche is the first menstrual cycle experienced by women. Ages of menarche variated, but normal in 13-14 years. The result of Health Research Association (Riskesdas) 2010 showed the average ages of menarche in Indonesia is 13 year. The purpose of this research was to determine the factor associated with the ages of menarche in female students of SMP Negeri 3 Sumbul by 2014. This research is an observational study with cross sectional approach.. Sample was many 126 students were taken by stratified random sampling. The research instrument used was a questionnaire as well as the scales of measuring instruments and gauges. Univariate data were analyzed descriptively and bivariate data were analyzed using the chi square test with 95% CI. The results showed the average ages of menarche is 13,67 years and the highest proportion of the ages of menarche of the respondent is normal(85,70%). The highest proportion of the responden is normal nutritional status (57,10%), mother ‘s ages of menarche is normal (84,90%), normal fisic activity (61,10%). The result of bivariate analysis, generally there is a significant association nutritional status (p = 0.024) and ages of menarche. There was no significant correlation between mother’s ages of menarche (p = 0,10), physical activity (p=0,65) and ages of menarche. It is suggested to SMP Negeri 3 Sumbul who have early to maintain healthy lifestyle so that risk factors for degenerative diseases such as breast cancer, ovarian cancer, uterine myomas and impact young marriage can be minimized. Keywords: Ages of menarche, nutritional status, physical activity